Single-Subject Research in Psychiatry: Facts and Fictions - Zuidersma, Marij; Riese, Harriëtte; Snippe, Evelien; Booij, Sanne H.; Wichers, Marieke; Bos, Elisabeth H. (Frontiers in Psychiatry, 2020)
Scientific evidence in the field of psychiatry is mainly derived from group-based (‘nomothetic’) studies that yield group-aggregated results, while often the need is to answer questions that apply to individuals. Particularly in the presence of great inter-individual differences and temporal complexities, information at the individual-person level may be valuable for personalized treatment decisions, individual predictions and diagnostics. The single-subject study design can be used to make inferences about individual persons. Yet, the single-subject study is not often used in the field of psychiatry. We believe that this is because of a lack of awareness of its value rather than a lack of usefulness or feasibility. In the present paper, we aimed to resolve some common misconceptions and beliefs about single-subject studies by discussing some commonly heard ‘facts and fictions’. We also discuss some situations in which the single-subject study is more or less appropriate, and the potential of combining single-subject and group-based study designs into one study. While not intending to plea for single-subject studies at the expense of group-based studies, we hope to increase awareness of the value of single-subject research by informing the reader about several aspects of this design, resolving misunderstanding, and providing references for further reading.